1973
DOI: 10.1139/v73-301
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Phosphorus Pentachloride with Ethyl-, Vinyl-, and Ethynyl(trichloromethyl)carbinol and with 1,1,1-Trichloro-3-nonyn-2-ol

Abstract: Reactions of phosphorus pentachloride with ethyl(trichloromethyI)carbinol (2), (trichloromethyl)-vinylcarbinol(7), ethynyl(trichloromethyl)carbinol (lla), and 1,l.l-trichloro-3-nonyn-2-01 ( l l b ) have been studied. Whereas the reaction of phenyl(trichloromethyl)carbinol with phosphorus pentachloride leads to a nearly quantitative replacement of the hydroxyl group by chlorine, the reactions of the aliphatic (trichloromethyl)carbinols are more complicated. Thus the reaction of 2 with phosphorus pentachloride g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…3 5~ of product (66% of Ethynyl(trichloromethyl)carbinol, I, l,l-trichloro-3-nonyn-2-01, (trichloromethyl)vinylcarb~nol, and ethyl(trich1oro-methy1)carbinol were synthesized as previously described (9).…”
Section: Ex~erimentalmentioning
confidence: 99%
See 1 more Smart Citation
“…3 5~ of product (66% of Ethynyl(trichloromethyl)carbinol, I, l,l-trichloro-3-nonyn-2-01, (trichloromethyl)vinylcarb~nol, and ethyl(trich1oro-methy1)carbinol were synthesized as previously described (9).…”
Section: Ex~erimentalmentioning
confidence: 99%
“…Accordingly, we report here on the reactions of these carbinols with methanolic potassium hydroxide, thiourea, cyanamide, and cold aqueous potassium hydroxide solution. We have previously reported on the reactions of the aliphatic-(trichloromethyl)carbinols with phosphorus pentachloride and shown that a wide variety of compounds are formed (9).…”
mentioning
confidence: 99%